2024
DOI: 10.3390/nu16040467
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a Smart Toy in Eating Disorder Treatment: A Pilot Study

Dimitri Chubinidze,
Zhuo Li,
Petr Slovak
et al.

Abstract: Individuals with eating disorders (EDs) often encounter challenges related to body image, emotional, and sensory difficulties during nutritional rehabilitation. To address these challenges, a novel technology-enabled smart toy, Purrble, designed for immediate assistance in emotion regulation, is being explored. A mixed-method approach involving workshops, diaries, and focus groups was employed to examine the feasibility of Purrble as a therapeutic tool and its impact on participants’ daily routines, sensory ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The therapeutic use of the novel technology-enabled smart toy Purrble, which is designed for emotional regulation, was explored in a mixed-method analysis by Chubinidze et al [ 15 ]. They found that it might be helpful particularly for patients with EDs and complex presentations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic use of the novel technology-enabled smart toy Purrble, which is designed for emotional regulation, was explored in a mixed-method analysis by Chubinidze et al [ 15 ]. They found that it might be helpful particularly for patients with EDs and complex presentations.…”
mentioning
confidence: 99%
“…The GDF-15 receptor GFRAL, which is known to be involved in appetite regulation, was found to be expressed across various central-nervous as well as peripheral tissues [ 12 ], and visfatin, S100B, and leptin are associated with the development of metabolic syndrome in people with bipolar depression [ 13 ]. Four articles of this Special Issue [ 14 , 15 , 16 , 17 ] summarized already available (e.g., nutritional interventions, psychological and family therapy) [ 14 ] and experimental (smart toy Purrble) [ 15 ] therapies for AN, effective therapies for the treatment of obesity (e.g., physical activity, dietary and nutritional intervention, cognitive behavioral therapy, clinical and self-monitoring) [ 16 ], as well as the preventive and therapeutic options for oral health consequences of EDs [ 17 ]. Witaszek et al’s finding that liraglutide and semaglutide were associated with increased cognitive restraint [ 8 ] is also therapeutically relevant as these GLP-1 receptor agonists are approved for the treatment of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation